The inequality-resource curse of conflict: Heterogeneous effects of mineral deposit discoveries - Joeri Smits; Yibekal Tessema; Takuto Sakamoto; Richard Schodde (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Despite a sizeable literature, there is no consensus as to whether and how mineral resources are linked to conflict. In this paper, we estimate the relationship between giant mineral deposit discoveries and the intensity of armed conflict (measured by battle deaths) around the world in the post-war era. The impact of such discoveries is potentially heterogeneous with respect to mineral commodity type: metals with a low value-to-weight ratio are not easy to exploit and smuggle and will disproportionally aid governments in their counterinsurgency efforts and raise the opportunity cost of fighting, whereas the discovery of deposits of high value-to-weight ratio metals may increase incentives for rebellion and make insurgency feasible. The data indeed show discoveries of giant deposits to lower the intensity of conflict for low unitvalue ores, but giant discoveries increase the intensity of conflict for high unit-value minerals. We also show that discoveries in countries with high ethnic inequality increase conflict intensity to a greater extent than in countries with low ethnic inequality - this heterogeneity is likely due to grievances related to the distribution of resource rents and revenues.
Keywords: 330; resource discovery; mining; ethnic inequality; conflict intensity